Outer membrane permeability of mcr-positive bacteria reveals potent synergy of colistin and macromolecular antibiotics against colistin-resistant Acinetobacter baumannii - Li, Meisong; Ma, Furong; Zhao, Hui; Zhou, Dianrong; Liang, Lujie; Lv, Runling; Li, Jiachen; Wang, Yaxuan; Xu, Lin; Liu, Chenfei; Tian, Guo-Bao; Feng, Siyuan; et al. (Frontiers in microbiology, 2024)
Colistin (CT) is the last-resort of antibiotic against multidrug-resistance (MDR) Acinetobacter baumannii ( A. baumannii ) infection. However, colistin resistance is increasingly reported in A. baumannii isolates partially due to the global emergence and dissemination of plasmid-borne mobile colistin resistance ( mcr ) gene and is a threat to human health. Thus, available treatment strategies urgently required in the fight against colistin-resistant A. baumannii . Here, we showed that mcr confers damaged outer membrane (OM) permeability in A. baumannii , which could compromise the viability of A. baumannii . Consistently, A. baumannii with colistin resistance exhibits increased susceptibility to macromolecular antibiotics such as rifampicin (RIF) and erythromycin (ERY). Moreover, the combination therapy of colistin and rifampicin demonstrates efficacy against colistin-resistant A. baumannii , regardless of the presence of mcr . Altogether, our data suggest that the synergy of colistin in combination with macromolecular hydrophobic antibiotics poses a promising therapeutic alternative for colistin-resistant A. baumannii .